2017
DOI: 10.18632/oncotarget.22234
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular glycogenotic foci after combined intraportal pancreatic islet transplantation and knockout of the carbohydrate responsive element binding protein in diabetic mice

Abstract: AimsThe intraportal pancreatic islet transplantation (IPIT) model of diabetic rats is an insulin mediated model of hepatocarcinogenesis characterized by the induction of clear cell foci (CCF) of altered hepatocytes, which are pre-neoplastic lesions excessively storing glycogen (glycogenosis) and exhibiting activation of the AKT/mTOR protooncogenic pathway. In this study, we transferred the IPIT model to the mouse and combined it with the knockout of the transcription factor carbohydrate responsive element bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…They reported that ChREBP binding is enriched in pathways involved in insulin signaling, adherent junctions and cancer, suggesting a novel involvement of ChREBP in tumorigenesis and cancer progression. Further, a recent study reported the importance of ChREBP in hepatocellular carcinoma (HCC) (Ribback et al, 2017). The authors found that genetic deletion of ChREBP (in ChREBP KO mice) impaired hepatocarcinogenesis driven by protein kinase B/Akt overexpression in mice.…”
Section: Activation Of Chrebp By Glucose Metabolitesmentioning
confidence: 99%
“…They reported that ChREBP binding is enriched in pathways involved in insulin signaling, adherent junctions and cancer, suggesting a novel involvement of ChREBP in tumorigenesis and cancer progression. Further, a recent study reported the importance of ChREBP in hepatocellular carcinoma (HCC) (Ribback et al, 2017). The authors found that genetic deletion of ChREBP (in ChREBP KO mice) impaired hepatocarcinogenesis driven by protein kinase B/Akt overexpression in mice.…”
Section: Activation Of Chrebp By Glucose Metabolitesmentioning
confidence: 99%
“…In light of these previous findings, considerable efforts should be devoted to identify key metabolic candidates whose inactivation might severely impair hepatocarcinogenesis while sparing normal cells. Previously, it has been demonstrated that alterations of glucose and lipid metabolism in HCC of humans and rodents are paralleled by the strong upregulation of carbohydrate-responsive element binding protein (ChREBP) transcription factor [13,19,20]. Together with the sterol regulatory element binding protein-1c (SREBP-1c) gene, ChREBP is a major positive regulator of glucose and lipid metabolism in the liver [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found an increased glycogen storage, reduced glucose-6-phosphatase activity and upregulated enzymes of glycolysis and de novo lipogenesis, beta-oxidation as well as overexpression of the insulin receptor and activated AKT/mTOR and Ras/MAPK pathways in CCF from both human livers and the rat model [20]. Similiarly, in the mouse, hepatocarcinogenesis is associated with activation of the insulin/AKT/mTOR signaling pathway, the transcriptional regulator ChREBP [16,21], as well as the lipogenic pathway [18,22,23]. Although these data hint to several pathways and regulators, a comprehensive inventory of gene and protein expression in human CCF is missing.…”
Section: Introductionmentioning
confidence: 76%